Analisis Pengaruh Berat Beban Muatan Terhadap Kinerja Sistem Kemudi pada Kendaraan Motor ATV 110 cc (All Terrain Vehicle) - Joko Susilo; Ikhwanul Qiram; Gatut Rubiono (Prodi Teknik Mesin Universitas PGRI Banyuwangi, 2022)
ATV is a vehicle with engine drive using a combustion engine, ATV is designed to have maneuverability supported by a lightweight and strong frame construction, a tough engine, and an adequate suspension system. Almost similar to cars, ATVs have applied Aeckermann's steering and independent suspension. At first ATVs were only used by plantation owners for their means of transportation, but along with the development of the times ATVs can be used for many activities in the automotive world such as racing, motorbikes for nature explorers, operational vehicles for the SAR team or in Indonesia many are rented out for cross-country activities at tourist sites. This study discusses the effect of the load on the performance of the steering system on a 110 cc ATV motorbike which is planned to be modified into an electric motor as the main engine. To measure the load on the performance of the design steering system using a digital dynamometer that is linked from the steering wheel to the ATV motor frame, to determine the weight of the steering wheel against the load, it is done with variations in the steering radius of 100, 150, 250, and 350 and giving a load of 0, 50, 75 kg. Later the digital dynamometer will read automatically when the variation of the experiment is carried out. The purpose of the study was to obtain the effect of the weight of the load on the performance of the motor steering system on a 110 cc ATV motor vehicle. In this study, changes in the load received by the steering wheel are expected to affect the magnitude of the moment to be received. This parameter is one of the performance of a steering system. The increase in payload causes the steering system to become heavier. This is due to the influence of the weight of the load pressing the seat (load point) which is forwarded to the vehicle frame, this is due to the gravitational force of the load on the vehicle, so that the steering system directly receives the load pressure which is transmitted to the tires. From this steering tire gets heavy friction from the road surface, so turning the steering wheel becomes heavy or difficult. Keywords: load, steering, ATV, performance